2023
DOI: 10.3390/molecules28135030
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Direct C–H Functionalization of Quinoxalin-2(1H)-Ones via Heterogeneous Catalysis Reactions

Abstract: In recent years, Web of Science has published nearly one hundred reports per year on quinoxalin-2(1H)-ones, which have attracted great interest due to their wide applications in pharmaceutical and materials fields, especially in recyclable heterogeneous catalytic reactions for direct C–H functionalisation. This review summarises for the first time the methods and reaction mechanisms of heterogeneous catalytic reactions of quinoxalin-2(1H)-ones, including six major types of heterogeneous catalysts involved. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The quinoxalin-2­(1 H )-ones are secondary metabolites of Streptomyces . Due to their diverse physical and pharmacological properties, they are used in a wide range of synthetic, pharmaceutical, and material chemistry applications . As a result of its inherent electrophilicity at the C3 position, quinoxalin-2­(1 H )-one has been extensively studied for radical-mediated C–H functionalization .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quinoxalin-2­(1 H )-ones are secondary metabolites of Streptomyces . Due to their diverse physical and pharmacological properties, they are used in a wide range of synthetic, pharmaceutical, and material chemistry applications . As a result of its inherent electrophilicity at the C3 position, quinoxalin-2­(1 H )-one has been extensively studied for radical-mediated C–H functionalization .…”
Section: Introductionmentioning
confidence: 99%
“…As a result of its inherent electrophilicity at the C3 position, quinoxalin-2­(1 H )-one has been extensively studied for radical-mediated C–H functionalization . In particular, the construction of a C–N bond at its C3 position via C–H functionalization is a key fragment for bioactive substances (Figure ) Previously, we had also carried out some research on the construction of C–N bonds at the C3 position of quinoxalin-2­(1 H )-one by the use of C–H functionalization . Recently, Ghosh’s group reported that KO t Bu-promoted C3-homocoupling of quinoxalin-2­(1 H )-ones generates symmetric dimers.…”
Section: Introductionmentioning
confidence: 99%
“…It is a low-melting solid (29-30 • C), soluble in water, and a weak base (pKa = 0.56) [15]. Several studies were performed and displayed a wide range of pharmacological activities for quinoxaline derivatives (Figure 1) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Additionally, quinoxalines are used for crop protection as a component of insecticides, herbicides, and fungicides [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%